(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes English vocabulary in modern technology, its distinctive features, and significance. The composition of digital age vocabulary, its development trends, and role in education are examined through literature analysis.